Assessment of awareness, practices, perceptions, and satisfaction of telepsychiatry among mental healthcare providers in Saudi Arabia - Omar A. Alshaikhi; Lujain A. Aldarsi; Ibrahim Abdullah A. Basfar; Alwaleed Alshehri; Raafat M. Shuqdar; Ramy Mohamed Ghazy; Ramy Mohamed Ghazy; Mahmoud Essam Elrggal (Frontiers in Psychiatry)
BackgroundTelepsychiatry, a global method for mental health services, has gained global attention, especially in the corona-virus diseases 2019 (COVID-19) era. It uses electronic communication and information technologies for remote psychiatric care, with synchronous modalities involving real-time interactions and asynchronous modalities allowing indirect communication. This study aimed to assess the awareness, practices, perceptions, and satisfaction of mental healthcare providers (MHPs) in the Kingdom of Saudi Arabia (KSA) regarding telepsychiatry utilization.MethodThis online, survey-based cross-sectional study included MHPs, both physicians and non-physicians, working in public and private mental health services across various regions of KSA. The study questionnaire was distributed using Google Forms via email and other popular social media platforms (including WhatsApp, Twitter, Telegram, and Facebook). The questionnaire was developed to assess the personal and socio-demographic characteristics of the participants, as well as their awareness, practices, perceptions, and satisfaction regarding telepsychiatry. Participants were recruited using convenience and snowball sampling techniques.ResultsOut of the 500 MHPs enrolled in the study, 52.2% were under 30 years, 52.6% were male, and 54.8% were single. Participants were from five regions: Central (27.6%), Western (22.6%), Eastern (22.0%), Southern (16.8%), and Northern (11.0%). Professionally, 33.8% were psychiatric residents, 21.8% were psychologists, 19.2% were social workers, and 12.6% each were psychiatric consultants and specialists. Of the study participants, 73.8% demonstrated awareness of telepsychiatry. More than three-fifths (63.7%) had previous practical experience. Among those with experience, 82.9% reported telepsychiatry practice durations of 3 years or less. Perception and satisfaction percentage scores for different domains indicated high perception regarding the advantages and disadvantages (62.6% ± 13.9) and improved patient access (75.2% ± 17.4). However, lower satisfaction scores were observed for MHPs’ access satisfaction (46.6% ± 11.7) and practice satisfaction (57.6% ± 9.6).Conclusion and recommendationMHPs in KSA exhibit high awareness but engage in telepsychiatry practice to a lesser extent. They have a good perception and are satisfied with their telepsychiatry practice. The study recommends that policymakers and stakeholders in KSA should prioritize building the capacities of MHPs in telehealth. Expanding and scaling up awareness activities are essential to improve digital literacy and telehealth practices among MHPs